A specific combination of dual index adaptors decreases the sensitivity of amplicon sequencing with the Illumina platform. (18th August 2020) - Hirose, Yuu; Shiozaki, Takuhei; Hamano, Itsuki; Yoshihara, Shizue; Tokumoto, Hayato; Eki, Toshihiko; Harada, Naomi
Abstract: Amplicon sequencing is a powerful approach in microbiome studies as it detects live organisms with high sensitivity. This approach determines the composition of sequence variants of marker genes using high-throughput DNA sequencers. The use of dual index adaptors is the fundamental technique for pooling DNA libraries for Illumina sequencers and is believed not to affect the results. However, here, we observed a decrease of sequence quality in samples containing a specific combination of indexes, namely N704 and S507 in Nextera kits, in multiple runs on the Illumina MiSeq sequencer operated in different facilities. This decrease was also observed when sequencing randomly fragmented DNA of Escherichia coli and was not observed when either individual adaptor was used. Each end of the DNA library with this index combination contains a complementary sequence motif, which potentially inhibits proper cluster generation and/or subsequent sequencing. Community analysis of the 16S and 18S rRNA amplicons using QIIME2 revealed significant decreases in α-diversity in the samples containing the N704/S507 index combination, resulting from loss of low-abundance sequence variants during denoising. Our data underscore the importance of quality validation of sequence reads in developing dual index techniques and suggest cautious interpretation of microbiome data containing low-quality sequence reads.